Analysis of teaching resources used in EFL classes in selected Ecuadorian universities - Acosta, Hazel; Cajas, Diego (Universitas Pendidikan Indonesia, 2018)
This study looks at how Communicative Language Teaching (CLT) is implemented in Ecuadorian universities through analysis of teaching resources that teachers use in classes. A survey was conducted through the administration of a questionnaire. A total of 65 teachers responded to the survey. The results indicated that in developing productive skills, group-oriented activities such as pair-and-share scheme and role-plays are frequently conducted, and the use of worksheets, translator applications and audio materials were often used in developing students’ receptive skills. Teachers did not often use resources on pronunciation activities, direction-oriented tasks and translation using Spanish. Analysis of frequently used resources showed that teachers tried to develop students’ communicative competence, one of the core principles of CLT, however, most of these resources were not teacher-made but support materials of textbooks produced by publishing houses abroad. Too much dependence on these resources influences teacher interaction with students and also diminishes the role of the teacher as the frontline source of language use especially in listening and speaking when audio materials and worksheets replace the teachers’ voice. Indeed, the selection of a teaching resource is as crucial as the method employed in CLT implementation in EFL classroom.